Implementing Clinic First Guiding Actions Across 4 Family Medicine Residency Clinics. (26th January 2022) - Adam, Patricia; Hersch, Derek; Peek, C.J.
Abstract : Problem: Family medicine faculty and residents have observed that continuity clinic is often unsatisfying, attributed to a lack of patient and team continuity and erratic clinic schedules pieced together after the prioritization of hospital service and rotation schedules. Approach: In 2019, a 3-year Clinic First project, called Clinic as Curriculum (CaC), was launched across the 4 family medicine residencies of the Department of Family Medicine and Community Health, University of Minnesota Medical School. The department began publishing quarterly CaC dashboard data. Each clinic completed a baseline assessment of their performance on the 13 Building Blocks of High-Performing Primary Care. Using their baseline data, each clinic identified which block or blocks, in addition to the blocks on continuity of care and resident scheduling, to focus on. The plan is to collaboratively implement the overall and local goals using dashboard data and iterative process improvement over 3 years. Outcomes: At baseline, clinics functioned quite well with respect to the 13 building blocks, but CaC dashboard data varied across the 4 clinics, with large variation between clinics on how frequently faculty were scheduled in the clinic and the proportion of total clinic visits seen by faculty. Resident continuity rates were low (range, 38%–47%). Level loading (consistent physician availability to meet patient demand) rates ranged from 1 to 11 days a month. Regarding resident schedules, 2 programs are moving from 4-week to 2-week inpatient blocks, and 2 programs are exploring longitudinal scheduling. One clinic will assign faculty and residents to specific clinic days. Two clinics are implementing microteams of 1 faculty and 3–4 residents. Next Steps: The authors plan to analyze the dashboard data longitudinally; explore microteams, team continuity, and team scheduling adherence; and develop and implement resident scheduling changes over the next 3 years.